Design of Structure and Control Algorithm for Solar Tracker - Huo Xiangru; Hou Li; Wei Yongqiao; Luo Lan; Zhang Qi (Jixie chuandong)
In order to alleviate the energy crisis,solar energy resources is widely developed and utilized.Improving the utilization of solar energy is an effective solution to alleviate the problem of energy. The solution is proposed from two aspects of the transmission precision and tracking precision of the solar tracking device.First of all,the secondary worm gear and worm drive program is applied to ensure the transmission accuracy of the mechanism. Then,the sun azimuth angle and height angle calculation formula under correction of installation error is applied to revise the tracking trajectory of the device. The tracking time nodes are selected by discrete selection method. Finally,the results of the experiments show that the structure design scheme and the tracking algorithm are of great significance for improving the utilization of solar energy.